Association between novel adiposity parameters and hyperuricemia: a cross-sectional study - Wang, Baoan; Ma, Chuncheng; Wu, Jinhua; Huang, Ze (Frontiers in Nutrition, 2025)
ObjectivesBody mass index (BMI) is a commonly used parameters to measure obesity, but it cannot well reflect the distribution of body fat, which has limitations in clinical practice. Novel adiposity parameters have emerged as substitution to BMI to assess obesity. This study aimed to comprehensively investigate the association between hyperuricemia and novel adiposity parameters.MethodsWe included data from the National Health and Nutrition Examination Survey from 1999–2006. Weighted logistic regression was employed to evaluate the relations between hyperuricemia and novel adiposity parameters, including body roundness index (BRI), weight-adjusted waist index (WWI), a body shape index (ABSI), and conicity index (CoI). To assess the most diagnostic factor for hyperuricemia, the receiver operating characteristic (ROC) curve analysis was employed. The area under the curve (AUC) was used to assess the diagnostic power of each parameter.ResultsThe study included 24,763 participants, 3,528 of whom were diagnosed with hyperuricemia. Compared with the first quartile (Q1), the fourth quartile’s (Q4) BRI, WWI, ABSI and CoI were linked to an increased risk of hyperuricemia (OR: 9.34, 95% CI: 7.73–11.28; OR: 4.67, 95% CI: 3.97–5.49; OR: 2.61, 95% CI: 2.26–3.02; OR: 7.34, 95% CI: 6.12–8.81, respectively). This relationship persisted after adjusting for confounding factors. Among the four novel obesity parameters, BRI had the largest AUC and was a good diagnostic index of hyperuricemia (AUC = 0.697 for male and AUC = 0.751 for female).ConclusionIn the general population, larger obesity parameters are linked to a higher risk of hyperuricemia. BRI has high diagnostic value and can be used as a new index for the evaluation of hyperuricemia. This study provides a new basis for the prevention and monitoring of hyperuricemia.